Level of Knowledge and Attitudes of Pulmonary Tuberculosis Patients Toward Medication Adherence in the Working Area of Ciwaruga Community Health Center - Annisa, Annisa; Dewi Wulantresna (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
Pulmonary tuberculosis (TB) remains a major public health issue in Indonesia, with treatment adherence varying among patients. The success of TB therapy is strongly influenced by patients’ knowledge and attitudes toward medication, as well as social and family support. This study aims to describe the level of knowledge and attitudes of pulmonary TB patients toward medication adherence at Ciwaruga Public Health Center in 2025. This research used a quantitative descriptive method involving 30 pulmonary TB patients undergoing anti-tuberculosis drug (OAT) treatment at Ciwaruga Public Health Center. Respondents were selected using purposive sampling. The research instruments consisted of a knowledge questionnaire (10 true–false items) and an attitude questionnaire (10 Likert-scale items). Data were analyzed using frequency distribution and percentage. Most respondents had moderate (43.3%) and high (40%) levels of knowledge, while 16.7% had low knowledge. Regarding attitudes, 46.6% had a fairly positive attitude, 36.7% had a good attitude, and 16.7% had a poor attitude. The analysis revealed that higher knowledge tends to be associated with more positive attitudes toward medication adherence. Patients’ knowledge and attitudes significantly affect their adherence to TB treatment. Continuous education, family involvement, and regular monitoring by health workers are essential to improve treatment outcomes.